Study Of Flip Chip Underfill Materials To Meet 260 Celsius High Temperature Reflow Requirement - Chin, Yoong Tatt (2002)
This project is to study the physical and thermo-mechanical of various underfills materials and its integration to the flip chip package. The objective of the project was accomplish by identifying key influencing factors in the underfill materials to meet 260 celsius high temperature reflow condition.